2021
DOI: 10.3390/jcm10143121
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Lymphedema Patients Can Still Benefit from Supermicrosurgical Lymphaticovenous Anastomosis (LVA) after Vascularized Lymph Node Flap Transfer (VLNT) as Delayed Lymphatic Reconstruction—A Retrospective Cohort Study

Abstract: Background: For lymphedema patients who received a vascularized lymph node flap transfer (VLNT) as their primary treatment, what are the treatment options when they seek further improvement? With recent publications supporting the use of lymphaticovenous anastomosis (LVA) for treating severe lymphedema, we examined whether LVA could benefit post-VLNT patients seeking further improvement. Methods: This retrospective cohort study enrolled eight lymphedema patients with nine lymphedematous limbs (one patient suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Regarding the post-LVA outcome, the present study showed significant volume reductions in the affected limbs of the older patients at six months and one year after LVA compared to the pre-LVA volume (both p < 0.001), On the other hand, there was no significant difference in volume reduction in the affected limbs between six months and one-year post-LVA ( p = 0.67). This finding suggested the occurrence of a relatively large degree of volume reduction within the first six months following LVA, which was consistent with that of our previous study focusing on assessing the outcome of LVA in patients who had previously received free lymph node flap transfer [ 41 ]. A possible explanation could be a post-LVA change in the lymphovenous pressure gradient.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the post-LVA outcome, the present study showed significant volume reductions in the affected limbs of the older patients at six months and one year after LVA compared to the pre-LVA volume (both p < 0.001), On the other hand, there was no significant difference in volume reduction in the affected limbs between six months and one-year post-LVA ( p = 0.67). This finding suggested the occurrence of a relatively large degree of volume reduction within the first six months following LVA, which was consistent with that of our previous study focusing on assessing the outcome of LVA in patients who had previously received free lymph node flap transfer [ 41 ]. A possible explanation could be a post-LVA change in the lymphovenous pressure gradient.…”
Section: Discussionsupporting
confidence: 91%
“…Other theories propose that the lymph nodes produce growth factors which stimulate regeneration of native and transferred lymphatic vessels and as a result create new lymphatic channels (Saaristo et al, 2012). Although numerous studies implied that the VLNT alone may even have greater potential than LVA (Akita et al, 2015; Cheng et al, 2018), there is evidence that combination of these both procedures might promise the best outcomes for the patients (Yang et al, 2021). In terms of prevention, the VLNT may require some time until the lymph flow is effectively restored.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that in advanced-stage lymphedema, suction-assisted lipectomy or VLNT combinations provide better results than lymphovenous anastomosis alone. 12 In addition, the absence of the breast in patients with breast cancer-related lymphedema is also a problem directly related to quality of life. Hence, the surgical method for lymphedema may also vary slightly depending on the patient’s need for delayed breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Consequently, in such cases, vascularized lymph node transfer (VLNT) through the free flap technique, in which lymph nodes collected from other parts of the body are transplanted to the edematous limb where lymphedema is occurring, has recently gained popularity, with various studies demonstrating its clinical usefulness. 11 , 12 Moreover, the physiological background of lymph node transfer has been elucidated through recent basic research. 13 , 14 Although several donor sites have been introduced and results have been reported, similar clinical outcomes and surgical risks have been reported for lymph node transfer from each donor site.…”
Section: Introductionmentioning
confidence: 99%